Analisa Kinerja Keuangan Perusahaan Sesudah Dan Sebelum Restrukturisasi Dengan Metode Economic Value Added (Studi Kasus Pt M) - Yoseano Adrianus dan Suwinto Johan (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
Maximize the profit, it was a belief that every financial worker knows in their mind while they work, even though in present day maximize the shareholder’s equity is the belief. There are many measurements to analyze financial performance of a company and EVA (Economic Value Added) was add to measure the company financial performance within year 2009 until 2016. In this study, PT M one of the well-known holding group company in Indonesia has facing a financial struggle within the internal company under the holding. So restructuring was decision to do on 2013 as turning point of the financial company. The result of the test with Wilcoxon signed ranked test is said that there is no difference between the company do restructuring or not do it. In fact, the financial performance of the company gotten worse for the restructuring process, but it is very dilemmatic inside the holding because if PT M not do the restructuring, one of the major division will collapse and giving threat to the holding company.